Pengembangan Hasil Produksi Oleh-Oleh Terhadap Peningkatan Pendapatan Umkm Di Kota Batu (Studi Kasus Pada Ud. Andhini) - Eka Farida; Muh Fahrurrozi; Neneng Rika Jazilztul Kholidah; Danang Prio Utomo (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
The purpose of this study was to determine the increase in MSME income in Batu in terms of the development of the production of souvenirs. The method used in this study is qualitative with descriptive analysis. The subjects of this study were informants who provided research data through interviews. The informant in this study is the owner of MSME business outlets namely UD. Andhini in Batu City. The analysis used is descriptive analysis. The results showed the development of the production of souvenirs typical of the city of Batu include fruit chips, apple jenang, apple dodol, potato chips, fruit juice drinks, and fruits experienced very rapid development. Some factors that drive the development of production are the characteristics of the product itself, increased purchasing power, the availability of resources with the required expertise, promising market share because as a tourism city, high return on investment and internal factors such as motivation, open personality and lifestyle changes. The development process has a direct impact on increasing the income of MSMEs in Batu. The increasing income of the people is sourced from the development of agriculture which is used as a fruit picking tourism area, home industry, and trade.